1995
DOI: 10.1084/jem.182.4.941
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus 1 envelope proteins induce interleukin 1, tumor necrosis factor alpha, and nitric oxide in glial cultures derived from fetal, neonatal, and adult human brain.

Abstract: Although microglia are the only cells found to be productively infected in the central nervous system of acquired immunodeficiency disease syndrome (AIDS) patients, there is extensive white and gray matter disease nonetheless. This neuropathogenesis is believed to be due to indirect mechanisms other than infection with human immunodeficiency virus 1 (HIV-1). Cytokines and toxic small molecules have been implicated in the clinical and histopathological findings in CNS AIDS. Previously, we have demonstrated in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(55 citation statements)
references
References 33 publications
2
52
0
Order By: Relevance
“…13,15 However, inappropriate expression of iNOS and overproduction of NO have adverse effects on the organism, these alterations participating in the onset of several pathologies such as various forms of neurodegeneration, chronic inflammation and autoimmune diseases. 18,19 For these reasons, the characterization of pathways involved in the negative regulation of macrophage activation constitutes a field of interest. 20 In this vein, inhibition by type I IFNs of iNOS expression has been described in macrophages stimulated in vitro with IFN-␥, and this has been explained in terms of the antagonism between type I and type II IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 However, inappropriate expression of iNOS and overproduction of NO have adverse effects on the organism, these alterations participating in the onset of several pathologies such as various forms of neurodegeneration, chronic inflammation and autoimmune diseases. 18,19 For these reasons, the characterization of pathways involved in the negative regulation of macrophage activation constitutes a field of interest. 20 In this vein, inhibition by type I IFNs of iNOS expression has been described in macrophages stimulated in vitro with IFN-␥, and this has been explained in terms of the antagonism between type I and type II IFNs.…”
Section: Introductionmentioning
confidence: 99%
“…Soluble gp41 has been shown to induce the production of proinflammatory cytokines such as TNF-␣ and IL-1 (17)(18)(19)(20)(21) and to increase the activity of nitric oxide synthetase in mononuclear phagocytes and glial cells (22). gp41 was also reported to suppress human lymphocyte proliferation (23) and to favor a Th2-type immune response by inducing IL-10 production in monocytes (24).…”
Section: T He Human Immunodeficiency Viruses Hiv-1 and Hiv-2 Destroy Cd4mentioning
confidence: 99%
“…No natural FPRL2 agonists have been identified. However, it has been demonstrated that Helicobacter pylori peptide Hp (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) activates the monocyte via FPRL2 (34).…”
Section: T He Human Immunodeficiency Viruses Hiv-1 and Hiv-2 Destroy Cd4mentioning
confidence: 99%
“…Increased intrathecal expression of pro-in¯am-matory cytokines has been associated with neuropathological changes in primate lentivirus infections (Genis et al, 1992;Koka et al, 1995;Lane et al, 1996). Similarly, MVV infection has been shown to induce expression of TNFa within brain tissues (Craig et al, 1997).…”
Section: Introductionmentioning
confidence: 99%